Translating the research diagnostic criteria for temporomandibular disorders into Malay: evaluation of content and process - Khoo, S.P.; Yap, A.U.J.; Chan, Y.H.; Bulgiba, A.M. (2008)
Aims: To develop a Malay-language version of the Axis II Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) through a formal translation/back-translation process and to summarize available data about the psychometric properties of the translated scales. Methods: To cross-culturally adapt the instrument, the RDC/TMD underwent translation using a forward-backward method. Subjects were recruited to test the congruency between translated and original versions of the RDC/TMD. The psychometric properties of 3 domains (Graded Chronic Pain Scale, Nonspecific Physical Symptoms, and Depression) of the RDC/TMD were examined, and the literature on this topic was reviewed. Results: All the items scored 93 to 100 congruency. Cronbacb's alphas for Graded Chronic Pain Scale, Nonspecific Physical Symptoms, and Depression were 0.77, 0.71, and 0.88, respectively (n = 40). The test-retest reliability of scores (intraclass correlation coefficient ICC) and levels (Spearman's rho) for these domains showed ICCs of 0.97, 0.94, and 0.95, respectively, with a lowest ICC value of 0.84 (n = 40); the Spearman's rho values were 0.93, 0.74, and 0.74, respectively. The discriminant validity between patients with pain symptoms (n = 40) and normal pain-free controls (n = 40) were statistically significant (P < .001). These correlations provide support for the internal consistency and validity of the Graded Chronic Pain Scale, Nonspecific Physical Symptoms, and Depression domains of the translated version of the RDC/TMD, which were found to be comparable to the psychometric properties of the original and other international translated versions. Conclusion: The cross-cultural adaptation of the RDC/TMD into the Malay language is suitable for use in Malaysia.